Determinants of Debt Financing Behavior in Indonesian Family Firms: The Moderating Role of Family Tribe’s Social Capital - Riffa'I Al Hakim; Yuni Utami; Mohammad Arridho Nur Amin (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2026)
This study aims to analyze the influence of Free Cash Flow (FCF), Operating Leverage (OL), and Market-to-Book Value (MBV) on debt financing behavior in 53 family firms listed on the Main Board of the Indonesia Stock Exchange for the 2021-2025 period. Additionally, this study examines the moderating role of Family Tribe’s Social Capital in these relationships. Using the Fixed Effects Model (FEM) panel data regression method via Stata 17 on 265 firm-year observations, the results indicate that FCF has a significant negative effect on debt financing behavior. Conversely, OL and MBV are found to have a significant positive impact on corporate financing decisions. Moderation analysis demonstrates that family tribal social capital significantly mitigates the influence of FCF and OL on debt policy, whereas no moderating effect was found in the relationship between MBV and debt policy. These findings confirm that sociological factors, specifically tribal identity, function as crucial informal governance instruments influencing strategic financial decisions in family firms within emerging markets.